Influence of silicification on the structural and biological properties of buffer-mediated collagen hydrogels - Quignard , Sandrine (2012)
A buffer-mediated gelation route for collagen hydrogels that allows the formation of homogeneous composite and hybrid materials with various silica sources (i.e., colloidal silica and soluble silicates) at high concentration (up to 25X10-3 M) is described. Most significant improvement in rheological properties and proliferation of primary adult human dermal fibroblasts was obtained for the silicate-based hybrid materials. A similar trend was observed in composite materials incorporating 14nm SiO2 nanoparticles, although to a much lesser extent, whereas larger colloids (80 and 390 nm) did not significantly impact mechanical stability and cell behavior. Modification of 80nm particles surface with amine groups weakens the collagen-mineral interface, resulting in the decrease of material stability and leading to particle aggregation during the course of cell proliferation experiments.